INFORMATION SYSTEM DESIGN PCB (PRINTED CIRCUIT BOARD) ON PT.SUKMA BETA SEMPURNA BEKASI - Sugito Sugito; Ir. Aqwam Rosadi Kardian (Jurnal Sistem Informasi, 1996)
With the rapid progress of technology development it will bring positive impact tothe other, as well as problems that exist show a package system can give moremeaning to that use, because the package design system or the new system can reducethe inefficient nature of work time or still manually.From a collection of some procedures that are written separately then we will get anew system that will be very helpful, because after all rolled into one and run thenthis will provide optimal capacity, because all the needs and conditions and facilitiesthat are available from the user of the system.